Minsan lng sila bata - Carolino, Ditsi; Buxani, Sadhana (Ditsi Carolino], 1996)
aThis video documentary is a personal journey into the world of working children in Philippine provinces. Dio and Tikoy slaughter pigs and cows in Cebu on graveyard shift. What the get in return is the fast scraped off from the animals' hides. Treatment farmer's kids Delena and Cito plant and Weed in the sugar hacienda in Ormoc to repay their families' debt. The catch is, there is no respect of ever finishing payment. Bobbi, Liting and Moklo, all small for their age, unload sack after sack of cement in 12 straight hours. This is a documentary about child labor in the Philippine provinces. The directors recorded small children working under excruciating conditions in slaughterhouses, sugarcane fields, and ship docks in order to add to their family income.